Synergistic effect of combining sunitinib with a peptide-based vaccine in cancer treatment after microenvironment remodeling. (31st December 2022) - Mougel, Alice; Méjean, Fanny; Tran, Thi; Adimi, Yasmine; Galy-Fauroux, Isabelle; Kaboré, Christelle; Mercier, Erwan; Urquia, Pauline; Terme, Magali; Tartour, Eric; Tanchot, Corinne
ABSTRACT: Although it has proven difficult to demonstrate the clinical efficacy of therapeutic vaccination as a monotherapy in advanced cancers, its combination with an immunomodulatory treatment to reduce intra-tumor immunosuppression and improve vaccine efficacy is a very promising strategy. In this context, we are studying the combination of a vaccine composed of peptides of the tumor antigen survivin (SVX vaccine) with the anti-angiogenic agent sunitinib in a colorectal carcinoma model. To this end, we have been focusing on administration scheduling and have highlighted a therapeutic synergy between SVX vaccine and sunitinib when the vaccine was administered at the end of anti-angiogenic treatment. In this setting, a prolonged control of tumor growth associated with an important percentage of complete tumor regression was observed. Studying the remodeling induced by each therapy on the immunological and angiogenic tumor microenvironment over time we observed, during sunitinib treatment, a transient increase in polymorphonuclear myeloid-derived suppressor cells (PMN-MDSCs) and a decrease in NK cells in the tumor microenvironment. In contrast, after sunitinib treatment was stopped, a decrease in PMN-MDSC populations has been observed in the tumor, associated with an increase in NK cells, pericyte coverage of tumor vessels and CD8 + T cell population and functionality. In conclusion, sunitinib treatment results in the promotion of an immune-favorable tumor microenvironment that can guide the optimal sequence of vaccine and anti-angiogenic combination to reinforce their synergy.